2021
DOI: 10.1016/j.jhin.2020.11.029
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro investigation into the release of fugitive medical aerosols into the environment during manual ventilation

Abstract: Background: During manual resuscitation, nebulizer therapy may be used to deliver therapeutics to patients in respiratory distress. However, the devices used to generate and deliver these medical aerosols have the potential to release these therapeutics into the local environment and expose caregivers to unwanted medical aerosols. Aim: To quantify the levels of fugitive medical aerosol released into the environment during aerosol drug delivery using a manual resuscitation bag with and without filtration. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…The addition of the capture filter to the expiratory port of the mouthpiece greatly reduced the release of fugitive aerosols into the atmosphere, with reductions in the peak values ranging from 47.3 to 77.7% for a normal breathing pattern and 61.3 to 83.6% for a distressed breathing pattern. Although the reductions were not as significant as those reported in other studies (Wittgen et al., 2006 ; Ari et al., 2016 ; McGrath et al., 2019a ; Mac Giolla Eain et al., 2021 ), the images and data highlight the effectiveness of filters in limiting the release and spread of fugitive aerosols.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The addition of the capture filter to the expiratory port of the mouthpiece greatly reduced the release of fugitive aerosols into the atmosphere, with reductions in the peak values ranging from 47.3 to 77.7% for a normal breathing pattern and 61.3 to 83.6% for a distressed breathing pattern. Although the reductions were not as significant as those reported in other studies (Wittgen et al., 2006 ; Ari et al., 2016 ; McGrath et al., 2019a ; Mac Giolla Eain et al., 2021 ), the images and data highlight the effectiveness of filters in limiting the release and spread of fugitive aerosols.…”
Section: Discussioncontrasting
confidence: 60%
“…However, preventing the release of said emissions at source would be the most effective means of protection. Using aerodynamic particle sizers (APSs) (McGrath et al., 2019a ; Mac Giolla Eain et al., 2021 ) quantified the release of fugitive medical aerosols during aerosol therapy. These works demonstrated that the addition of capture filters on the expiratory ports of face masks and mouthpieces and use of vibrating mesh nebulizers over jet nebulizers yielded mass concentration levels similar to ambient levels.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of providing nebulized therapies to COVID-19-infected people, several publications have provided guidance and practical strategies over the last two years [7][8][9][10][11][12]. They mostly advocate for appropriate consideration for the inhaled medication delivery method, including the type of nebulizer (standard jet, vibrating mesh, and breath-actuated devices) and breathing interfaces (mouthpiece versus a facemask) [7,8,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%